Protective effect of quercetin and lypoate of functional groups on proteins in retina with experimental diabetes - Pasechnikova, N.V.; Moroz, O.A. (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Relevance of the work is to study of influence of quercetin and lypoate on treatment with experimental diabetes. Purpose. To study the effect of quercetin and lipoate on thiol groups of proteins in experimental diabetes. Methods. Studies were conducted on white rats. Experimental animals were divided into four groups: first — control group (14 rats), the second — experimental group (14 rats), animals with diabetes, without the use of drugs, the third — the experimental group (12 rats), animals with diabetes, and the use of lipoic acid, the fourth — the experimental group (15 rats), animals with diabetes and the use of quercetin. In retinas homogenates produced determination of thiol groups of proteins. Results. Application of preparations of lipoic acid and quercetin prevents the fall-off of level of thiol groups of proteins of retina. In the mechanism of this effect undoubtedly an important role is played by their antioxidant properties. Conclusion. 1. It is set that at development of streptozotocin diabetes the making progress decline of thiol groups of proteins of retina and increase of disulfide bridges are marked, i.e. oxidization of sulfhydryl groups. 2. Application of lipoic acid and quercetin prevents the considerable decline of level of thiol groups of proteins of retina for animals with streptozotocin diabetes, here marked the most expressed effect for animals in a two-month period of development of experimental diabetes after application of lipoic acid, when differences in the level of thiols were statistically meaningful.